Employing television press conferences to introduce national issues An analytical study of the television press conferences of former Prime (Journal of the College of Basic Education, 2022)
Television press conferences represent one of the most important effective communication tools or activities that government agencies of all levels and degrees resort to in order to reach the public through various media outlets, in particular television and inform them about the latest developments on the most prominent issues and important topics or current events and the role of government agencies in explaining Its circumstances, its treatment, and the expression of its policy towards these issues or events, from here this research came to shed light on the use of television press conferences as a source of information that the workers of the conference take as a means and a tool for introducing the national issues raised in it, how to address them and export them to the public.